2002
DOI: 10.1007/s12110-002-1003-8
|View full text |Cite
|
Sign up to set email alerts
|

Girl helpers and time allocation of nursing women among the Toba of Argentina

Abstract: In this paper we outline the activities of young girls in a Toba community of northern Argentina and examine the effect of girl helpers on time allocation of nursing women. Activity budgets were obtained for 41 girls aged 3 to 15 using spot observations. Girls spent substantial portions of observations engaged in helping behaviors. Individual values varied with age, anthropometric characteristics, and birth order. Activity budgets of 21 nursing women were obtained through focal observation sessions. Women livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…As documented in other studies (Bove et al, 2002;Hawkes et al, 1997;Kramer, 2005;Quinlan et al, 2003), older children and related adults, especially the women's mothers or mothers-in-law (i.e., grandmothers), provided greater support. Older children, mostly females, and grandmothers helped with domestic tasks such as childcare, food preparation, and cooking and both male and female children and other adult women and men helped with subsistence activities.…”
Section: Maternal Strategies In Biosocial Contextsupporting
confidence: 60%
See 1 more Smart Citation
“…As documented in other studies (Bove et al, 2002;Hawkes et al, 1997;Kramer, 2005;Quinlan et al, 2003), older children and related adults, especially the women's mothers or mothers-in-law (i.e., grandmothers), provided greater support. Older children, mostly females, and grandmothers helped with domestic tasks such as childcare, food preparation, and cooking and both male and female children and other adult women and men helped with subsistence activities.…”
Section: Maternal Strategies In Biosocial Contextsupporting
confidence: 60%
“…Anthropologists have demonstrated how the help of kin can affect maternal time allocation. Bove et al (2002) found that lactating Toba women with girl helpers spent less time conducting domestic work than women without such support. Gray (1995) noted that Turkana women with fewer children and co-wives spent more time in herding activities than those in larger, wealthier households.…”
mentioning
confidence: 97%
“…It has also been demonstrated that opposite-sex siblings have more conflict than do same-sex siblings (Dunn and Kendrick 1982;Campione-Barr and Smetana 2010). Older sisters often serve as caretakers to young siblings (Bove et al, 2002), and several studies suggest that sister-sister relationships are typically closer than brother-sister ones (Pollet 2007;White and Riedman 1992a), which also fits with studies that suggest a more kin-oriented role for women in general (Hrdy 2005;Daly 1996, 1998). It is also the case, however, that same-sex individuals are theoretically in more direct conflict as they are more likely to be in competition over the same resources whereas opposite-sex siblings are less likely to be competing over the same resources.…”
Section: What Factors May Influence Whether a Sibling Is Seen As A Resupporting
confidence: 55%
“…body size and fertility) as opposed to stored, inherited wealth. Fertility rate was estimated as the inverse of closed interbirth intervals for the Ache (Hill & Hurtado 1996), Aeta (Migliano et al 2007), Agta (Early & Headland 1998), Aborigines in Arnhem land (Billington 1948;Hamilton 1981), Baka ( Yamauchi et al 2000), Gambian villagers (Billewicz & McGregor 1981;Sear et al 2003), Guaja (G. Djurovic 2005, unpublished data), Hadza (Blurton Jones et al 1992), Hiwi ( Hurtado & Hill 1987), Ju/'hoansi ( Howell 1979), Maku-Nadeb (R. S. Walker 2003, unpublished data), Toba (Bove et al 2002), Tsimane (M. Gurven 2003, unpublished data), Turkana (Little et al 1983), West African 'Pygmies' (Cavallli-Sforza 1986) and Yanomamo ( Neel & Weiss 1975). The Ache were allowed to enter the sample twice, as hunter-gatherers in earlier research and as horticulturalists on a reservation in more recent research.…”
Section: Methodsmentioning
confidence: 99%